Theorizing conceptualizations of literacy development from classroom practice : an exploration of teachers' theory revision - Mashatole, Mogakabane Abram (My University, 2014)
This research was a case study of teachers’ conceptualizations and theories that underpin their classroom practices in a primary school in the Mankweng Township, Limpopo Province. The study sought to explore what these conceptualizations are, and what theoretical paradigms (or mix of paradigms) underpin them. However, rather than attempt to get teachers to articulate their conceptions (which may be too abstract and difficult an undertaking), teachers were required to engage with classroom practices different from their own and in the context of this engagement, confront their own beliefs about literacy and literacy development. The study also aimed to explore whether encounters by teachers with classroom practices based on sets of principles different to their own will lead them to revise their theories or principles underpinning their teaching practices. The empirical data was in the form of seven lessons by the regular teachers alongside six intervention lessons taught by the academic researchers. Key to the research design was to get teachers to critically and reflectively engage with their teaching and the teaching of others. Through the use of actual transcripts of teachers’ classroom practices and responses to the two sets of lessons as evidence, teachers’ classroom practices, actions and beliefs were made visible in this research. The data from regular lessons show a consistent yet disconcerting pattern in teachers’ classroom practices as learners were found to be writing far too little, and much of learning and teaching was predominantly oral. Teachers also seemed to lack theories of literacy teaching, and thus could not meaningfully engage their learners in academic discourse enabling them to cross the bridge between everyday knowledge and academic knowledge. Overall, the study suggests that pedagogic and content knowledge are key, in order to empower teachers with both knowledge of their disciplinary content and meaningful strategies of communicating the knowledge they have to their learners. Further current models of teacher professionalization through short training workshop do not seem to be very effective and alternative approaches need to be developed.
Thesis (M.A.(Translation and Linguistics)) -- University of Limpopo, 2014
Keywords: Classroom practice; Conceptualisation; Teachers; Classroom environment; Classroom management; Observation (Educational method)